CEMENT OF THE CONNECTORS BUILDING AND IN BUILDINGS APPLICATION SECTORS ANALYSIS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This in the article cement gardeners building and in buildings to be used related main directions, building and buildings under construction basis and foundations task, them calculation for elementary information and from them targeted use opportunities about word goes.